Direct Oral Anticoagulants for the Treatment of Acute Venous Thromboembolism Associated with Cancer: A Systematic Review and Meta-Analysis - Giustozzi, Michela; Agnelli, Giancarlo; del Toro-Cervera, Jorge; Klok, Frederikus A.; Rosovsky, Rachel P.; Martin, Anne-Céline; Herold, Joerg; Tzoran, Inna; Szmit, Sebastian; Bertoletti, Laurent; Becattini, Cecilia; Huisman, Menno V. (Thrombosis and Haemostasis, 2020)
Background International guidelines have endorsed the use of edoxaban or rivaroxaban as an alternative to low-molecular-weight heparin (LMWH) for the treatment of acute venous thromboembolism (VTE) in cancer patients. Recently, a large randomized controlled trial of apixaban versus dalteparin in patients with cancer was completed. We performed an updated meta-analysis to assess the efficacy and safety of direct oral anticoagulants (DOACs) versus LMWH in patients with cancer-associated VTE.Methods MEDLINE, EMBASE, and CENTRAL (Cochrane Controlled Trials Registry) were systematically searched up to March 30, 2020 for randomized controlled trials comparing DOACs versus LMWH for the treatment of VTE in patients with cancer. The two coprimary outcomes were recurrent VTE and major bleeding at 6 months. Data were pooled by the Mantel–Haenszel method and compared by relative risk ratios (RRs) and 95% confidence intervals (CIs).Results Four randomized controlled studies (2,894 patients) comparing apixaban, edoxaban, or rivaroxaban with dalteparin were included in the meta-analysis. Recurrent VTE occurred in 75 of 1,446 patients (5.2%) treated with oral factor Xa inhibitors and in 119 of 1,448 patients (8.2%) treated with LMWH (RR 0.62; 95% CI 0.43–0.91; I2, 30%). Major bleeding occurred in 62 (4.3%) and 48 (3.3%) patients receiving oral factor Xa inhibitors or LMWH, respectively (RR 1.31; 95% CI 0.83–2.08; I2, 23%).Conclusion In patients with cancer-associated VTE, oral factor Xa inhibitors reduced the risk of recurrent VTE without a significantly higher likelihood of major bleeding at 6 months compared with LMWH.
Keywords: direct oral anticoagulants; oral factor Xa inhibitors; cancer; dalteparin; meta-analysis; venous thromboembolism